The effect of using nanofluids on triangular microchannel heat exchanger performance - Bhaskaran G.; Mohammed H.A.; Shuaib N.H. (2023)
A numerical study is performed to study the effects of using various types of nanofluids on a triangular shaped microchannel heat exchanger (MCHE). The performance of an aluminum MCHE with various types of nanofluids such as Al 2O3, CuO, SiO2, Ag and TiO2 and diamond particles with particle volume fraction of 2% using water as base fluid is comprehensively analyzed. The three-dimensional steady, laminar developing flow and conjugate heat transfer of a balanced MCHE were solved using finite volume method. In order to maintain laminar flow in the microchannels, Re number was ranged from 100 to 800. The other parameters tested in this study include the effects of Reynolds number towards the temperature, effectiveness and pressure drop of the MCHE. It is found that nanofluids have improved the temperature profile and heat transfer rate of the MCHE. The increase in pressure drop was minimal while the thermal and hydrodynamic performance of the heat exchanger was enhanced. Copyright 2010 by ASME.